Effects of solasodine of Solanum melongena peel origin in the treatment of palmar arsenical keratosis - Sultana, Razia; Misbahuddin, Mir (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This study was conducted to confirm the effect of the ointment containing Solanum melongena peel extract in the treatment of palmar arsenical keratosis and to identify the compound responsible for the effect. In total, 30 patients with moderate to severe palmar arsenical keratosis were enrolled according to the inclusion criteria. Extract from S. melongena peel was obtained and a topical ointment was prepared from the extract and supplied at the field level at an interval of two weeks. Instruction was given to the patients about how to apply the ointment. Adherence and adverse effects of the treatment were monitored regularly through phone calls and during each visit. The mean (± SD) size of the keratotic nodules was 21.9 ± 10.0 mm2 before intervention and 6.6 ± 5.3 mm2 after intervention. The percentage of reduction was 69.8. Nuclear magnetic resonance spectroscopy, infrared spectroscopy, liquid chromatography-mass spectrometry and elemental analysis of the extract was done to identify the compound and solasodine, a steroidal alkaloid, was identified.